Bridging Faith and Innovation: A Systematic Literature Review of Islamic FinTech Adoption Patterns and Regulatory Frameworks (2020-2024) - Suswanto, Riza Eko; Wahyudi, Ickhsanto; Rahmawati, Rahmawati; Said, Muhammad (Al-Muamalat: Jurnal Ekonomi Syariah, 2025)
This systematic literature review examines the development of Islamic Financial Technology (Islamic FinTech) adoption and its regulatory frameworks across various jurisdictions. Through a comprehensive analysis of recent literature from 2020-2024, this study investigates the key factors influencing Islamic FinTech adoption, regulatory challenges, and market growth opportunities. The review encompasses 28 scholarly articles focusing on Islamic FinTech implementation, adoption factors, and regulatory frameworks. The findings reveal that trust, religious orientation, and technological readiness significantly influence Islamic FinTech adoption. Additionally, the study identifies critical challenges, including Shariah compliance mechanisms, regulatory frameworks, and consumer protection. The novelty of this study lies in its systematic and holistic approach, integrating the analysis of adoption factors, regulatory challenges, and technological innovations within the context of Islamic FinTech. The research emphasizes the importance of developing a comprehensive regulatory framework that balances technological innovation with Shariah compliance, while ensuring consumer protection. This study contributes to the advancement of knowledge on Islamic FinTech by providing practical insights for policymakers, practitioners, and researchers in developing a sustainable Islamic FinTech ecosystem. Furthermore, the study offers concrete recommendations, such as the harmonization of international Shariah standards and the utilization of blockchain technology to enhance transparency, which can be applied in a global context.